2020
DOI: 10.25046/aj050483
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Approach for Automatic Topic Classification in an Online Submission System

Abstract: Topic classification is a crucial task where knowledge categories exist within hierarchical information systems designed to facilitate knowledge search and discovery. An application of topic classification is article (e.g., journal/conference paper) classification which is very useful for online submission systems. In fact, numerous online journals/magazine submission systems usually receive thousands of article submissions or even more for each month. This leads to a huge amount of time-consumption of editors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Previous researches on short text classification [6][7][8][9] showed that deep learning are recommended. Thus, in this experiment we evaluated commonly utilized of deep learning architectures such as LSTM, Bi-LSTM, and CNN with a baseline comparison of non-deep learning approach of logistic regression.…”
Section: Evaluate Classification Performancesmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous researches on short text classification [6][7][8][9] showed that deep learning are recommended. Thus, in this experiment we evaluated commonly utilized of deep learning architectures such as LSTM, Bi-LSTM, and CNN with a baseline comparison of non-deep learning approach of logistic regression.…”
Section: Evaluate Classification Performancesmentioning
confidence: 99%
“…Thus LDA alone is not enough for handling short texts. Classification with short texts usually takes deep learning to address the subject context's insufficiency [6,7]. Since graph as a data structure is beneficial in highlighting the subject context, the deep learning approach evolves into a neural network with spatial moves on graph nodes called graph convolutional network (GCN).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation